KESEJAJARAN BENTUK PENERJEMAHAN FRASA BAHASA ARAB DALAM CERAMAH HABIB UMAR BIN HAFIDZ - Hensa Utama, Muhammad Apridho; Masrukhi, Moh. (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2022)
This study described the forms of Arabic phrases and the formal correspondence of Arabic phrases in Habib Umar bin Hafidz's lectures. This research is translational research using qualitative data and descriptive methods. The data source is the initial 13 minutes of the 47minutes video from the YouTube channel Al-Bahjah TV entitled